The Legal Responsibility of Hospitals in Medical Malpractice Cases After the Issuance of the Health Law in 2023 - Vitrianingsih, Yeni; Dwi Miarsa, Fajar Rachmad; Yahya, Dhofirul (LEGAL BRIEF, 2025)
Medical malpractice has serious consequences for patients and creates a legal burden on hospitals as healthcare institutions. This article aims to analyze the form and limits of hospital legal responsibility in cases of medical malpractice based on a normative approach to laws and regulations in Indonesia, especially Law No. 17 of 2023 concerning Health and Government Regulation No. 28 of 2024 concerning Implementing Regulations of the Health Law. This research uses a normative qualitative method with a legislative and conceptual approach. The results of the study show that hospitals can be held held accountable civilly, criminally, and administratively, especially in the framework of vicarious liability, where the hospital is responsible for the actions of medical personnel under its authority. However, there are still weaknesses in the implementation of regulations and gaps between legal norms and field practice. Therefore, it is necessary to strengthen the supervision system, internal medical evaluation, and legal protection for patients and medical personnel